2018
DOI: 10.1093/eurpub/cky218.272
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and use of Copenhagen Burnout Inventory in Italian sample of University Professors

Abstract: Academics often have to face with burnout syndrome at work. This cross-sectional study evaluates the reliability of the Italian version of the Copenhagen Burnout Inventory (CBI) in a sample of Academics of Sapienza University of Faculty of Medicine and Pharmacy, through an online questionnaire composed of the CBI, SF12 Health Survey, and Positivity Scale. Univariate, bivariate, multivariate analyses, and Cronbach α coefficients of CBI were performed. Ninety-five participants completed the questionnaire (respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Higher scores indicate more burnout. Validity and reliability have been reported by Sestili et al (2018), who found Cronbach's alpha 0.892, 0.868 and 0.836 for the three subscales, respectively. We obtained reliability of 0.905, 0.830 and 0.884 for the subscales in our research.…”
Section: Methodsmentioning
confidence: 55%
“…Higher scores indicate more burnout. Validity and reliability have been reported by Sestili et al (2018), who found Cronbach's alpha 0.892, 0.868 and 0.836 for the three subscales, respectively. We obtained reliability of 0.905, 0.830 and 0.884 for the subscales in our research.…”
Section: Methodsmentioning
confidence: 55%
“…Job burnout has been stated as having a possible adverse impact on nurses’ performance, work satisfaction and QWL [ 76 ]. It also has been reported that job burnout is also present among academics, in particular those who belong to public universities [ 77 ]. On the one hand, a high QWL has been associated with greater productivity at the workplace [ 50 ].…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
“…For purposes of the CBI, the term client is understood in the appropriate context as “patient” (as opposed to customer or colleague). There is high internal reliability of the CBI, the questions are easy to understand and answer and it has been shown to correlate well with SF-36(24). In this study we used the CBI in 2 ways, initially as described under statistical analysis, we broke down the linear regression by the average score of individual questions.…”
Section: Introductionmentioning
confidence: 99%